Aqueous and alcoholic extracts of Artemisia annua L. improved insulin resistance via decreasing TNF-alpha, IL-6 and free fatty acids in high-fat diet/streptozotocin-induced diabetic mice - Mahshid Ghanbari; Forouzan Sadeghimahalli (Mashhad University of Medical Sciences, 2022)
Objective: Type 2 diabetes mellitus (T2DM) is a metabolic disease that influences many people worldwide.  Management of insulin resistance in T2DM without side effects of chemical drugs, is the ultimate goal of the medical community. Artemisia annua L. is used for the treatment of diabetes in folkloric medicine. The present study investigated the effects of aqueous and alcoholic extracts of A. annua (AA) on insulin resistance in high-fat diet/STZ-induced diabetic mice.Material and methods:  Mice were divided into groups including control with a normal diet, un-treated high-fat diet/streptozotocin-induced diabetic mice, and diabetic mice treated by oral administration of 100, 200, and 400 mg/kg body weight of water (hot and cold) and alcoholic extracts of AA.  After four weeks of treatment with AA, blood sampling was carried out to measure factors involved in insulin resistance such as low-density lipoprotein/ High-density lipoprotein (LDL/HDL) ratio, free fatty acids, Tumor necrosis factor alpha (TNF-alpha), interleukin-6 (IL-6), and homeostasis model assessment of insulin resistance (HOMA-IR) as an index of insulin resistance.Results: The results showed that all AA extracts (100, 200, and 400 mg/kg) and metformin (250 mg/kg) significantly reduced the serum levels of free fatty acids, TNF-alpha, IL-6, LDL/HDL ratio, and HOMA-IR in diabetic mice compared to untreated diabetic mice (p<0.0001). Notably, the 400 mg/kg dose of cold-water extract was more effective than metformin in reduction of TNF-alpha and IL-6 (p<0.01 and p<0.05, respectively).Conclusion: These data illustrated that AA extracts attenuated insulin resistance by reducing the lipid profile and adipocytokines.